An e-government capability model for government employees. (1st January 2014) - Zarei, Behrouz; Saghafi, Fatemeh; Zarrin, Leila; Ghapanchi, Amir Hossein
Stakeholder involvement in e-government projects is a critical success factor in creating e-government. Technology-based natures of e-government and current technological changes have brought about a change in the needs of stakeholders. The capability approach emphasises the potential effects of stakeholders on improvement of development programmes. This issue has received little attention from e-government researchers. The purpose of this article is to investigate the effects of e-government implementation on the capabilities and functions of government employees. In this paper, first, the main capabilities are recognised and classified. Then the functions that are created as the consequences of these capabilities are identified. Next, a model is formed and analysed using statistical analysis. The results showed that achievement of electronic government can affect 13 capabilities in the government employees. Furthermore, the results demonstrated that the most important influential factors on e-governing are, respectively, better exploiting the environment, the ability to produce goods and render public electronic services, the ability to establish efficient institutions in the information society, the ability to render services with electronic quality, and the ability to learn through e-learning.